Mustard's operation for patients with ventriculoarterial concordance. Report of two cases and a cautionary tale. Issue 4 (April 1985) - Arciprete, P; Macartney, F J; de Leval, M; Stark, J
Abstract : Three patients with ventriculoarterial concordance and an abnormal atrioventricular connexion were investigated. One patient had total anomalous pulmonary venous connexion to a left vertical vein. In 1972 this was repaired and a ventricular septal defect was closed, but the presence of atrioventricular discordance was missed and the patient died. In the other two patients, Mustard's operation resulted in survival. One patient had situs solitus and atrioventricular discordance with an associated ventricular septal defect, which was closed. The other had left isomerism (quasi solitus) with an ambiguous atrioventricular connexion (quasi discordant). A previously noted ventricular septal defect had spontaneously closed.